PERANCANGAN IKLAN TV PENERBIT BUKU SALEMBA CABANG SUMATERA BARAT - ADRI NOFRIANSYAH, Dr. Budiwirman, M.Pd., Hendra Afriwan, S.Sn., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The Publisher is an industry that is concentrated in the areas of produce and eproduce a paper or literature. Design promotion Publisher Salemba Branch West umatra through the medium of TV advertising as the major media because the media are most easy to found a society at the moment is TV Television Commercial. The concept of TV advertising's future themed traveling because reading a book we can venture out and explore the world more. Methods used in the collection of data is by holding interviews, observation, and documentation, while the method of the approach used in the design is a SWOT analysis (strenght, weakness, opportunity, treath). Design promotion in the form of TV ads it will be equipped with several media such as posters, supporting the X-Banner, T-shirt, CD labels, calendars, stickers and key chains.Keywords: Publisher, Salemba, TV Commercials